Analysis of the Influence of Dynamic Capabilities on Company Performance Mediated By Competitive Advantage - Yohanes Yohanes; Farah Margaretha; Yvonne Augustine Sudibyo (Green Publisher Indonesia, 2021)
This research has a purpose to find out how the influence of Dynamic Capabilities, either directly or indirectly on Company Performance through Competitive advantage as a mediating variable. Design / methodology / approach – data collection in the form of distributing questionnaires to collect a sample of 309 manufacturing companies in Indonesia. In any case, to analyze the data, the analytical method used is the Structural Equation Model (SEM) to assign the phenomenon and the tool used is AMOS 22. The result of this research is that Dynamic Capabilities, affect the upgrade in Competitive Advantage significantly and positively. Dynamic Capabilities, affect the positive and significant upgrade in Company Performance. Competitive Advantage affects the Company's performance improvement positively and significantly. The mediating influence of Competitive advantage upgrades the influence of Dynamic Capabilities, on improving Company Performance. Practical implications – this research has shown that Dynamic Capabilities have affected Company Performance through the practice of Competitive Advantage. In any case, This research describes that the company's performance is influenced by different competitive priorities as well as internal capabilities and external capabilities. Originality / value - This research analyzes sustainable innovation predicated on dynamic capabilities in manufacturing companies in Indonesia, by collecting managers' perceptions of modification in the external environment that affect the adaptation and alignment of the company's maneuver, which has an impact on the applied business model.